SUSAN S. BENJAMIN, MICHELANGELO SABATINO - Modern in the Middle: Chicago Houses 1929-1975 - Garcia-Requejo, Zaida (ZARCH, 2022)
Susan S. Benjamin, Michelangelo Sabatino Modern in the Middle: Chicago Houses 1929-1975Nueva York: The Monacelli Press, 2020. 296 p. Tapa dura. Idioma: inglés. 60 $ ISBN 978-1-58093-526-5